Tendensi Sosial di Balik Perumpamaan Unik Lukas: Analisis Tematis Lukas 9:51–19:44 - Prabowo, Paulus Dimas; Kalaka, Jhon (Sabda: Jurnal Teologi Kristen, 2023)
This article entitled "Social Tendencies Behind Luke's Unique Parable: Thematic Analysis of Luke 9:51–19:44" is a review to answer the meaning behind the inclusion of Luke's unique parable in chapter 9:51–19:44. This section is interesting because it is a narrative leading up to Jesus' death. The parable in it is similar to the last will of someone who will soon die. Several scholars have proposed various interpretations regarding the meaning of this unique parable. Through thematic analysis and literature study methods, it was found that the unique parable in Luke 9:51–19:44 has a social tendency, where the gospel is related to social equality, social concern, and social consequences. Luke pays more attention to social life in his gospel. AbstrakArtikel berjudul “Tendensi Sosial di Balik Perumpamaan Unik Lukas: Analisis Tematis Lukas 9:51–19:44” ini merupakan sebuah ulasan untuk menjawab makna di balik pencantuman perumpamaan unik Lukas di dalam pasal 9:51–19:44. Bagian ini menarik karena merupakan narasi menjelang kematian Yesus. Perumpamaan di dalamnya berupa wasiat terakhir dari seseorang yang akan segera mati. Beberapa sarjana telah mengusulkan beragam tafsiran mengenai makna perumpamaan unik tersebut.  Melalui metode analisis tematik dan studi literatur, ditemukan hasil bahwa perumpamaan unik dalam Lukas 9:51–19:44 memiliki tendensi sosial, dimana injil berkaitan dengan kesetaraan sosial, kepedulian sosial, dan konsekuensi sosial. Lukas menaruh perhatian yang lebih terhadap kehidupan sosial di dalam Injilnya.